Acquisition of k- and λ- carrageenan from macroalgae chondracanthus chamissoi and its aplication in the food industry - Salas De La T., Norma (2008)
The exploitation of algae producing carrageenan are intensified since the 80 '. Obtaining κ-carrageenan and λ-carrageenan is a function of the proper selection of algae, correct identification of the stages of life, control of parameters such as temperature, pH, time, concentration of solutions. The extraction process is based on: soluble in hot water and insolubility in polar organic solvents. Gametophyte phase is a starting point for the production of κ-carrageenan and phase sporophitic is geared to the production of λ - carrageenan. The ability gelling (κ-carrageenan) and performance viscosante (λ-carrageenan) of carrageenan are characteristics that apply to gelificar or thicken aqueous systems.